2019
DOI: 10.1108/vjikms-04-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

A model for examining the role of the Internet of Things in the development of e-business

Abstract: Purpose Nowadays, the Internet of Things (IoT) offers new intelligent services and business model opportunities by extending the internet connectivity into physical devices and daily objects. Recently, this technology has had a deep impact on all the aspects of human societies from industry to management and business. Therefore, the purpose of this paper is to predict the impact of using IoT services on the development of electronic business (e-business). Design/methodology/approach For evaluating the model’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Another survey that aimed to investigate the performance of management in a company concluded that the quality of data directly increases the overall strategic performance of the company [47]. Furthermore, Ghouchani et al (2019) [48] noticed that the quality and security of IoT tools as well as users' knowledge of Information Technology (IT) have a positive impact on the development of e-Business.…”
Section: System Qualitymentioning
confidence: 99%
“…Another survey that aimed to investigate the performance of management in a company concluded that the quality of data directly increases the overall strategic performance of the company [47]. Furthermore, Ghouchani et al (2019) [48] noticed that the quality and security of IoT tools as well as users' knowledge of Information Technology (IT) have a positive impact on the development of e-Business.…”
Section: System Qualitymentioning
confidence: 99%
“…E-commerce is the buying and selling of goods and services, or the transmitting of funds or data, over an electronic network, primarily the internet. The following four factors affect the long-term sustainability of e-commerce in the IoT [57,58]:…”
Section: E-commerce Sustainabilitymentioning
confidence: 99%
“…E-commerce (electronic commerce) is the buying and selling of goods and services, or the transmitting of funds or data, over an electronic network, primarily the internet. The following four factors affecting the long-term E-commerce sustainability in IoT have to emphasize [40,41]:…”
Section: E-commerce Sustainabilitymentioning
confidence: 99%